The potency of multiple synchronous ipsilateral tumours on quantity of axillary lymph node involvement in clinical early stage breast cancer (Annals of Medical Research, 2022)
Aim: The purpose of this study was to compare multiple synchronous ipsilateral breast cancer (MSIBC) with unifocal breast cancer (UBC) in terms of the quantity of axillary lymph node involvement (ALNI) and to examine the factors that increase the number of ALNI in MSIBC.Materials and Methods: Patients who were diagnosed with clinical early-stage breast cancer (stage I, II) with cN0 were included in the study.Results: Patients were divided into two groups according to multifocality (MSIBC, n=142, 26.2%; UBC, n=400, 73.8%). Statistically significant differences in ALNI were found between the two groups (p < 0.001). Patients with MSIBC had significantly higher number of total positive lymph nodes, involvement of three or more axillary lymph nodes, tumor size, intermediate-high grade tumor, microcalcification, lymphovascular invasion (LVI), and accompanying ductal carcinoma in situ (DCIS) than patients with UBC (p < 0.001, p < 0.001, p < 0.001, p = 0.041, p < 0.001, p < 0.001, p = 0.035, respectively). Out of the 142 patients who had MSIBC, 107 (75.4%) had ≤ 2 ALNI and 35 (24.6%) had > 2 ALNI. Presence of pT2 tumor, grade 2/3 tumor, C-erbB2 positivity, microcalcification, and LVI for MSIBC patients with > 2 ALNI were significantly higher than patients with ≤ 2 ALNI (p = 0.003, p < 0.001, p = 0.048, p < 0.001, p = 0.002, respectively). Presence of pT2 tumor, microcalcification, LVI, and grade 2/3 tumor were found to be significant after multivariate analysis for > 2 ALNI in MSIBC patients.Conclusion: These results show that MSIBC not only increases ALNI in breast cancer patients, but also increases the number of involved lymph nodes. In MSIBC, limited axillary sampling can be performed more safely by identifying subgroup patients that may have increase number of ALNI.
Keywords: Breast cancer; Multicentric; Multifocal; Unifocal; Axillary lymph node